Tracheal bronchus: a rare cause of recurrent pneumonia in adults. Issue 7 (27th July 2022) - Mishra, Mayank; Kumar, Arjun
Abstract : Tracheal bronchus, also known as bronchus suis, is a rare congenital anomaly of the airway where an accessory bronchus originates directly from the trachea. With an estimated incidence of 0.001%–2.0%, this condition is rarely reported in literature. It is usually discovered as an incidental finding in an otherwise asymptomatic individual. However, it can act as a focus of recurrent infection or present as persistent radiographic infiltrates. Multidetector CT imaging and bronchoscopy play a crucial role in the identification of this entity. We hereby report the case of a middle-aged man who presented with recurrent right upper lobe pneumonia, which was found to be due to an underlying tracheal bronchus.